A queer arrangement of school: Using spatiality to understand inequity - Schmidt, Sandra J (Journal of curriculum studies, 2015)
This manuscript contributes to a discussion of how to meaningfully engage issues of sexuality in the curriculum. Noting the struggle to create social change through the inclusion of LGBQ people and events, the manuscript is premised on what we might learn about equity and change by locating the study of inequity in how it is etched into and reproduced through engagements with space. The manuscript uses a mapping study to explore how students produce school in contested and multiple ways. This method is both model for how to engage with space in the curriculum and as a tool that changes how we recognize queer subjects in our discussions of equity and inclusion.